Human parvovirus B19-induced anaemia in pre-school children in Ilorin, Nigeria - Oluwaseyi S. Ashaka; Olajide O. Agbede; Adesuyi A. Omoare; Samuel K. Ernest (AOSIS, 2018)
Sera collected from 57 anaemic and 115 non-anaemic age-matched pre-school children in Ilorin, Nigeria, between November 2014 and December 2015 were assayed for human parvovirus B19-specific IgM antibodies by using the enzyme linked immunosorbent assay technique. A total of 17 (29.8%) anaemic children and 18 (15.7%) non-anaemic children were positive for parvovirus B19 infection. Infection with parvovirus B19 is common in this population, and screening for the virus during differential diagnosis is recommended.